PLANNING OF INNOVATIVE DEVELOPMENT OF CHEMICAL ENTERPRISES BASED ON ENERGY ENTROPY APPROACH - J. Antokhina; A. Vikulenko; A. Kolesnikov (Вестник Северо-Кавказского федерального университета, 2022)
The article describes the characteristics of entropy and negentropy and calculates the negentropic balance with the replacement of energy indicators with monetary ones. The application considers 5 laws of energy-entropics and assesses energy-entropics and management of a relatively separate system - a chemical enterprise: it considers the distance method, which makes it possible to evaluate innovative development of production based on «economic thermodynamics::, splitting the profit growth formula and planning innovative development of chemical production.